1998
DOI: 10.1038/sj.bjp.0702002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an atypical muscarinic cholinoceptor mediating contraction of the guinea‐pig isolated uterus

Abstract: 1 In many smooth muscle tissues a minor M 3 -muscarinic acetylcholine (mACh) receptor population mediates contraction, despite the presence of a larger M 2 -mACh receptor population. However, this is not the case for guinea-pig uterus where radioligand binding and functional studies exclude a dominant role for M 3 -mACh receptors. 2 Using tissue from animals pre-treated with diethylstilboestrol, estimates of antagonist a nity were made before and after selective alkylation procedures, together with estimates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
2
14
1
Order By: Relevance
“…The muscarinic acetylcholine receptor antagonist affinities (pK i values) obtained in the caput and cauda epididymis were compared with those obtained by Doods et al [40]. In addition, the pK i values for methoctramine obtained in the present study in the caput (7.80 Ϯ 0.15) and cauda epididymis (7.26 Ϯ 0.11) were comparable to those reported in tissues that express muscarinic M 2 receptors, such as rat vas deferens (pK i ϭ 8.4 [46]), smooth muscle cell culture from human prostate (pK i ϭ 8.1 [47]), and guinea pig uterus (pK i ϭ 7.5 [40], and pK i ϭ 8.1 [48]). Both analyses indicated that muscarinic acetylcholine receptors detected in the epididymis have a highly significant correlation with the M 2 receptor subtype.…”
Section: Discussionsupporting
confidence: 69%
“…The muscarinic acetylcholine receptor antagonist affinities (pK i values) obtained in the caput and cauda epididymis were compared with those obtained by Doods et al [40]. In addition, the pK i values for methoctramine obtained in the present study in the caput (7.80 Ϯ 0.15) and cauda epididymis (7.26 Ϯ 0.11) were comparable to those reported in tissues that express muscarinic M 2 receptors, such as rat vas deferens (pK i ϭ 8.4 [46]), smooth muscle cell culture from human prostate (pK i ϭ 8.1 [47]), and guinea pig uterus (pK i ϭ 7.5 [40], and pK i ϭ 8.1 [48]). Both analyses indicated that muscarinic acetylcholine receptors detected in the epididymis have a highly significant correlation with the M 2 receptor subtype.…”
Section: Discussionsupporting
confidence: 69%
“…An early example is that several antidepressants such as chlorimipramine potently inhibited H 2 receptor-mediated stimulation of cAMP formation in the homogenates of guinea pig hippocampus but failed to affect the cAMP formation in the slice preparations (Dam Trung Tuong et al, 1980). The pharmacological profile of mAChRs mediating carbachol-induced contraction in the guinea pig and rat uterus was not in agreement with the profile obtained from radioligand binding studies with the homogenates (Boxall et al, 1998;Munns and Pennefather, 1998). In the rat stomach mucosa, M 1 mAChRs could be detected in the tissue segments but were undetectable in the homogenates (Anisuzzaman et al, 2008a).…”
Section: And 3)mentioning
confidence: 65%
“…However, there have been several reports of "atypical" pharmacological profiles in which anomalous estimates of the functional affinity of receptors for antagonists in native tissues play a significant role in defining these atypical phenotypes of mAChRs (Nelson and Chal-liss, 2007). For example, in the guinea pig and rat uterus the functional affinities for mAChR antagonists are not in agreement with the affinities of M 2 mAChRs identified in radioligand binding studies, suggesting a possible involvement of an atypical operational mAChR in cholinergic contraction (Boxall et al, 1998;Munns and Pennefather, 1998). In addition, certain mAChR antagonists, such as darifenacin and solifenacin that are used in the management of overactive bladder, display in vivo selectivity for inhibition of mAChRmediated urinary bladder contraction relative to salivary secretion, even though both responses are mediated by the same M 3 mAChR subtype (Abrams et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…In guinea‐pig uterus, evidence for the presence of muscarinic M 2 ( Eglen et al ., 1989 ; 1992 ; Doods et al ., 1993 ), M 3 ( Leiber et al ., 1990 ), M 4 (Dörje et al ., 1991) and an atypical muscarinic receptor ( Boxall et al ., 1998 ) has been presented. The rabbit uterus has not been extensively studied but M 2 , M 3 and M 4 receptors have been identified using immunoprecipitation techniques ( Crankshaw, 1984 ; Dörje et al ., 1991 ).…”
Section: Introductionmentioning
confidence: 99%